Titin truncating mutations: A rare cause of dilated cardiomyopathy in the young. (March 2016) - Fatkin, Diane; Lam, Lien; Herman, Daniel S.; Benson, Craig C.; Felkin, Leanne E.; Barton, Paul J.R.; Walsh, Roddy; Candan, Sukru; Ware, James S.; Roberts, Angharad M.; Chung, Wendy K.; Smoot, Leslie; et al.
Abstract: Truncating mutations in the TTN gene are the most common genetic cause of dilated cardiomyopathy in adults but their role in young patients is unknown. We studied 82 young dilated cardiomyopathy subjects and found that the prevalence of truncating TTN mutations in adolescents was similar to adults, but surprisingly few truncating TTN mutations were identified in affected children, including one confirmed de novo variant. In several cases, truncating TTN mutations in children with dilated cardiomyopathy had evidence of additional clinical or genetic risk factors. These findings have implications for genetic testing and suggest that single truncating TTN mutations are insufficient alone to cause pediatric-onset dilated cardiomyopathy.